2017
DOI: 10.1016/j.envres.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

The impact of BMI on non-malignant respiratory symptoms and lung function in arsenic exposed adults of Northern Chile

Abstract: Background Elevated body mass index (BMI) and arsenic are both associated with cancer and with non-malignant lung disease. Using a unique exposure situation in Northern Chile with data on lifetime arsenic exposure, we previously identified the first evidence of an interaction between arsenic and BMI for the development of lung cancer. Objectives We examined whether there was an interaction between arsenic and BMI for the development of non-malignant lung disease. Methods Data on lifetime arsenic exposure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Another study has demonstrated that As-associated FVC reduction is observed on males ( Khan et al, 2020 ). In addition, overweight and obesity were shown to aggravate As-induced lung dysfunction ( Nardone et al, 2017 ). Moreover, impaired lung function in As-exposed children ( Ahmed et al, 2017 ) and adults ( Wang et al, 2020 ; Shih et al, 2020 ) was also associated with lung inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Another study has demonstrated that As-associated FVC reduction is observed on males ( Khan et al, 2020 ). In addition, overweight and obesity were shown to aggravate As-induced lung dysfunction ( Nardone et al, 2017 ). Moreover, impaired lung function in As-exposed children ( Ahmed et al, 2017 ) and adults ( Wang et al, 2020 ; Shih et al, 2020 ) was also associated with lung inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found the relationship of As with hypertension, high cholesterol (Hall et al, 2017;Mendez et al, 2016) and reported presence of As in auricle and mammary artery tissues of As exposed CHD patients (Roman et al, 2011). Research also showed associations between As and decreased lung function and elevated respiratory symptoms (Dauphine et al, 2011;Nardone et al, 2017;Steinmaus et al, 2016). Multiple studies found negative influence of As on diabetes outcomes such as type 2 diabetes (Castriota et al, 2018;Del Razo et al, 2011) although no association was observed between As exposure and gestational diabetes (Munoz and Valdes, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of 751 adults aged 39-60 years from Northern Chile reported high BMI (above 90 th percentile or >33.9 kg/m 2 ) and high WAs above 11 μg/L to be risk factors for respiratory symptoms. The study revealed an increased risk of respiratory symptoms such as cough (OR=10.7, 95% CI: 3.03, 50.1), shortness of breath (OR=14.2, 95% CI: 4.79, 52.4), and wheeze (OR=14.4, 95% CI: 4.80, 53.7) (Nardone et al, 2017) associated with high BMI and As exposure. Observations were similar in the same geographic region among 765 adults (>40 years), who spent 80% of their lives in three cities including Antofagasta.…”
Section: Pulmonary Effects-respiratory Outcomes Investigated In Chile Andmentioning
confidence: 93%
“…As shown in Table 1 , VC and FVC were higher than normal value in all BMI subgroups expect for BMI < 18.5 group. Previous studies showed that FVC% had positive relationship with BMI in children while had negative association with BMI in normal and overweight adults [ 19 , 20 , 21 ]. Low level of lung function detected in this study may be attributed to malnutrition during childhood and the consequently low BMI at the adult stage.…”
Section: Discussionmentioning
confidence: 99%